2018
DOI: 10.1123/rsj.2017-0038
|View full text |Cite
|
Sign up to set email alerts
|

Practice Makes Perfect: Student Employee Transferable Skill Utilization in Campus Recreation

Abstract: Student employment is a vital aspect of development for many college students during their matriculation. This exploratory study examined the self-reported utilization of desirable transferable skills by student employees in a variety of campus recreation settings. A survey of 417 campus recreation student employees was conducted, asking how often different transferable skills were utilized within the course of their employment. While it is recognized that no one environment may be able to provide for all tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…This provides on-site staff the opportunity to deliver the quickest appropriate response until more advanced care can arrive and take over. Furthermore, from a student development standpoint, acquiring these certifications can act as important transferrable skills for student employees (Anderson et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…This provides on-site staff the opportunity to deliver the quickest appropriate response until more advanced care can arrive and take over. Furthermore, from a student development standpoint, acquiring these certifications can act as important transferrable skills for student employees (Anderson et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Our findings indicated some differences in the current literature. For example, Anderson et al (2018) found the length of employment and age could affect students' transferable skills. Therefore, our finding implies future research efforts are needed as current literature showed limited studies and inconsistent findings on student employees' working experience and their continuous growth of various transferable skills, especially in specialized program areas in campus recreation.…”
Section: Discussionmentioning
confidence: 99%
“…The questionnaire was developed based on previous studies of campus recreation student employees' working experience and demographics (Anderson et al, 2018) and adapted the Council for the Advancement of Standards in Higher Education's (CAS's) Framework for Assessing Learning and Development Outcomes (FALDO; Strayhorn et al, 2006) for student instructors' leadership development, relationship building, and communication skills. The first draft of the questionnaire was sent for experts' review, including three campus recreation supervisors and three university faculty in recreation and sport-related disciplines.…”
Section: Measurementsmentioning
confidence: 99%
“…First, consistent with previous studies (McGinty et al, 2008; Royal & Rossi, 1996), the result of this study showed that the more CRC employees experienced SOC, the more they experienced job satisfaction regardless of their job classification and tenure. Considering CRC workplace that needs employees working as a team and have a lot of interactions with employees and participants (Anderson et al, 2018; Scola et al, 2017), CRC employees may easily develop SOC in their workplace, and it can influence the levels of their job satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…It may negatively affect the satisfaction of operating conditions. In addition, scholars have stated that CRC managers should monitor and help student employees and other employees (Anderson et al, 2018; Kampf, 2013; Turner et al, 2005). Although CRC professional employees work with student employees, they should need to monitor as a supervisor, and it can be pressure for them.…”
Section: Discussionmentioning
confidence: 99%